Perkembangan Sosial, Emosi, Moral Anak dan Implikasinya Terhadap Pembentukan Sikap Sosial SIswa Sekolah Dasar - Ani Siti Anisah; Sapriya; Kama Abdul Hakam; Ernawulan Syaodih (Jurnal Ilmu Pendidikan Dasar Indonesia, 2021)
This study aims to determine (1) the characteristics of social, emotional, and moral development in elementary school children, and (2) the implications of children's social, emotional, and moral development on the formation of social attitudes in elementary school children. The research method used in this study is literature. The results showed that the characteristics of social, emotional, and moral development of elementary school children were aware of the social roles, religion, race, and socioeconomic status of their peers, accepted cultural stereotypes, and adult attitudes towards their status, thus creating group awareness in their social environment. These characteristics will persist until late childhood and will continue until they are adults if educators provide a stimulus in continuing their mature developmental tasks. The stimulus is in the form of guidance, direction, and providing a good and healthy socio-cultural environment in social, emotional, and moral development so that it has implications for the formation of good social attitudes. For children's socialization skills to improve, the task of educators is to guide and direct them to learn to accept and carry out responsibilities, learn to compete with others, learn good social behavior, learn to work together, learn from adults, and learn with peers, learn to adapt themselves with group standards, learn to play to develop physical, learn to share, and learn sportsmanship. The most important thing is good parenting from parents as the first madrasa for children informing children with noble character as a form of good social attitude in society.